Open-Access Textbooks and Financial Sustainability: A Case Study on Flat World Knowledge - Hilton III, John; Wiley, David (International Review of Research in Open and Distributed Learning, 2011)
Many college students and their families are concerned about the high costs of textbooks. A company called Flat World Knowledge both gives away and sells open-source textbooks in a way it believes to be financially sustainable. This article reports on the financial sustainability of the Flat World Knowledge open-source textbook model after one year of operation.